Theoretical and Experimental Study of Freeze-Drying of "Loco" (Concholepas Concholepas) - Reyes-Salinas, A; Mahn-Osses, A (2011)
The "loco" is a mollusk somewhat similar to abalone that exists exclusively in Chile and Peru. Given the high commercial value of loco, preservation through freeze-drying seems economically viable. In this work, the freeze-drying process of loco meat was analyzed theoretically and experimentally. The effects of particle size, freeze-drying pressure, and intermittent use or not of microwave in the secondary drying stage, on the extent of the freeze-drying period, rehydration properties, shrinkage and texture were investigated by using a 23 factorial design. Drying and rehydration kinetics were adjusted to phenomenological models in order to determine mass transfer parameters. Freeze-drying pressure significantly affects the extent of the drying process. Freeze-drying pressure results in shrinkage, while microwave produces a volume increase. The effective moisture diffusivity (Deff) estimated form drying curves fluctuated between 10-10 and 10-11 (m2/s), agreeing with values reported for other meat products. The adjustment of the rehydration kinetics to the Constant Diffusivity Model gave the best fit, resulting in Deff in the order of 10-10 (m2/s). Particle size and freeze-drying pressure significantly affected rehydration capacity. © 2011 Taylor & Francis Group, LLC.